Adsorption analysis : equilibria and kinetics - Duong, D. Do (Imperial College Press, 1998)
This book covers topics of equilibria and kinetics of adsorption in porous media. Fundamental equilibria and kinetics are dealt with for homogeneous as well as heterogeneous particles. Five chapters of the book deal with equilibria and eight chapters deal with kinetics. Single component as well as multicomponent systems are discussed. In kinetics analysis, we deal with the various mass transport processes and their interactions inside a porous particle. Conventional approaches as well as the new approach using Maxwell-Stefan equations are presented. Various methods to measure diffusivity, such.
Keywords: Adsorption.; Porous materials.; Gases -- Absorption and adsorption.; Solids -- Surfaces.; Chemical engineering -- Data processing.; Adsorption; Gaz -- Absorption et adsorption.; Génie chimique -- Informatique.; adsorption.; TECHNOLOGY & ENGINEERING -- Chemical & Biochemical.; SCIENCE -- Chemistry -- Industrial & Technical.; Chemical engineering -- Data processing; Gases -- Absorption and adsorption; Porous materials; Solids -- Surfaces